2009
DOI: 10.1080/13825580902871034
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the Within-Person Coupling of Reading Vision and Cognition in the Elderly

Abstract: This study examined the within-person relationship between reading vision and cognitive functioning. Analysis was conducted on 36 community-dwelling elderly (age range = 60-87) who completed a reading vision task and three cognitive tests (i.e., Rey Auditory Verbal Learning Task (AVLT), Letter Series, and Number Comparison) twice a day over 60 consecutive days. Significant within-person variability was found for the reading vision measure. Additionally, a main effect was found for reading vision and performanc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
16
1

Year Published

2010
2010
2015
2015

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 11 publications
(17 citation statements)
references
References 28 publications
0
16
1
Order By: Relevance
“…The total score ranged from 0 to 35 with 35 signifying the highest level of cognitive function. Persons with relatively low cognitive function may place a lower value on good vision, e.g., read less often, 24 be less future-oriented or be less able to comprehend the potential consequences of not getting recommended care. 25 …”
Section: Methodsmentioning
confidence: 99%
“…The total score ranged from 0 to 35 with 35 signifying the highest level of cognitive function. Persons with relatively low cognitive function may place a lower value on good vision, e.g., read less often, 24 be less future-oriented or be less able to comprehend the potential consequences of not getting recommended care. 25 …”
Section: Methodsmentioning
confidence: 99%
“…Intraindividual variability has been observed across several physical and mental health parameters. Specifically, intraindividual variability has shown to be a reliable and quantifiable index of cognitive performance (Allaire & Marsiske, 2005;Hultsch, MacDonald, & Dixon, 2002), affect (Kuppens, Van Mechelen, Smits, De Boeck, & Ceulemans, 2007), stress (Neupert, Almeida, Mroczek, & Spiro, 2006), control beliefs (Neupert & Allaire, 2012), sensorimotor functioning (Li, Aggen, Nesselroade, & Baltes, 2001), blood pressure (Gamaldo, Weatherbee, & Allaire, 2008), sleep (Gamaldo, Allaire, & Whitfield, 2010), vision (Weatherbee, Gamaldo, & Allaire, 2009), and daily activities (Ghisletta, Nesselroade, Featherman, & Rowe, 2002).…”
mentioning
confidence: 99%
“…A recent study estimated that a mild decline in hearing ability is equivalent to an increase of 6.8 years in chronological age in terms of the negative effects on cognitive function (Lin et al 2011 ). Similarly, studies have found that poorer visual function in older adults is related to worse fluid intelligence and memory span, (Clay et al 2009 ), and to diminished episodic memory, reasoning, and speed of processing (Weatherbee et al 2009 ). Thus, it appears that an important consequence of degradations in sensory processing is a robust compromise in cognitive processing.…”
Section: Negative Neuroplasticity In Agingmentioning
confidence: 94%